2009
DOI: 10.1021/mp800148u
|View full text |Cite
|
Sign up to set email alerts
|

Toward anIn VivoDissolution Methodology: A Comparison of Phosphate and Bicarbonate Buffers

Abstract: Purpose To evaluate the difference between the pharmaceutical phosphate buffers and the gastrointestinal bicarbonates in dissolution of ketoprofen and indomethacin, to illustrate the dependence of buffer differential on biopharmaceutical properties of BCS II weak acids, and to recommend phosphate buffers equivalent to bicarbonates. Methods The intrinsic dissolution rates of, ketoprofen and indomethacin, were experimentally measured using rotating disk method at 37°C in USP SIF/FaSSIF and various concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 40 publications
(75 reference statements)
3
90
0
Order By: Relevance
“…with pKa values of 4.40, 4.76 and 4.15 for Ibu, Ket and Trf, respectively (Sheng et al, 2009). Performed measurements gave an estimation of drugs solubility 257 under studied experimental conditions: at pH 2 and 37 ºC, measured solubility values were in the order of 0.06, 0.26 and 0.69 mg mL-1 for Ibu, Ket and 258 Trf(T), respectively, while at pH 6.7 and 37 ºC, the solubility of the three compounds was higher than 0.7 mg mL-1, which was the highest value assayed.…”
Section: Drug Dissolution and Release Profiles 252mentioning
confidence: 99%
“…with pKa values of 4.40, 4.76 and 4.15 for Ibu, Ket and Trf, respectively (Sheng et al, 2009). Performed measurements gave an estimation of drugs solubility 257 under studied experimental conditions: at pH 2 and 37 ºC, measured solubility values were in the order of 0.06, 0.26 and 0.69 mg mL-1 for Ibu, Ket and 258 Trf(T), respectively, while at pH 6.7 and 37 ºC, the solubility of the three compounds was higher than 0.7 mg mL-1, which was the highest value assayed.…”
Section: Drug Dissolution and Release Profiles 252mentioning
confidence: 99%
“…Phosphate buffer has an effective pKa of 7.19 and a resultant higher buffer capacity (23 mmol/L/∆pH) thus provides greater driving force for the acidic polymer dissolution than that of bicarbonate with a pKa of 6.31 and a much lower buffer capacity (3.1 mmol/L/∆pH). Sheng et al has also suggested that pKa differences in these two buffer species results in different buffer capacity at the solid-liquid interface; where phosphate buffer had about 23 % higher buffer capacity relative to the bicarbonate, at the same pH and buffer concentration [35]. Ionic strength of the dissolution media also have a profound effect on the reaction rate between the polymer film and the basic buffer species; a drastic change in the dissolution rate has been reported from enteric coated formulations with change in ionic strengths of the media [15,23,29].…”
Section: Distinct Behaviour Of Enteric Formulations In Physiological mentioning
confidence: 99%
“…GM in vitro release from cross-linked and co-cross-linked microparticles was evaluated in a pH 3.0 medium for 2 h and, then, in pH 7.4 Tris-HCl buffer for 4 h in order to simulate the pH conditions of the gastrointestinal tract ( Figure 5). By considering that phosphate buffer species, having a chelating action on calcium, are disconnected with the principal physiological species in the human GI tract (Dressman & Reppas, 2000;Sheng et al, 2009), Tris-HCl buffer was selected instead of phosphate buffer. The cross-linked microparticles provided a three-phase profile showing a negligible GM release at pH 3.0 and a burst effect (∼ 60%) followed by a gradual release phase at pH 7.4.…”
Section: In Vitro Drug Release Studymentioning
confidence: 99%